Workshop Pemahaman Gen Z tentang Banjir dan Pencegahan - Sinaga, Daniel Rodiaman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Flooding is an event that occurs as a result of the accumulation of water and cannot be accommodated by the soil.Flooding in Jakarta has become a routine problem over time, due to natural and human factors faced by the DKI Jakarta community.Losses caused by floods, especially indirect losses Not only the physical impacts suffered by the community but also non-physical losses such as schools being demolished, prices of basic necessities rising, and sometimes even deaths. Kodoatie and Syarief (2006) provide some examples of flood impacts or losses, loss of life or injury, property loss, settlement damage, trade area damage, industrial area loss, agricultural land damage, drainage and irrigation system damage, road and railway damage, highways, bridges, and airports damage, telecommunications system damage. Then the DKI Jakarta Regional Government coordinates with the Central Government to address the problem, the flood management policies are divided into short, medium and long-term periods. (Handayani, 2013). In this service to the community, there is an understanding of flooding and persecution using the method of devotion to the society in the form of socialization. This activity was followed by 24 people of the Generation Z, this Socialization has the theme “Flood Prevention and Management”. The purpose of this socialization is to expect the generation Z to gain a better understanding of the Flood and to emphasize the sense of self-awareness not to take actions that aggravate the flood.